1996
DOI: 10.1103/physreva.53.2587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coherent coupling of autoionizing states on multiphoton ionization

Abstract: Uiterwaal, Cornelis J.; Fotakis, C.; Bachau, H.; Sanchez, I.; and Cormier, E., "Effects of coherent coupling of autoionizing states on multiphoton ionization" (1996) Phys. Rev. A 53, 2587Rev. A 53, -2597Rev. A 53, (1996 [ We present the experimental and theoretical investigation of the effects of the strong electromagnetic coupling of two autoionizing states (AIS's) on the photoionization properties of an atomic system. These effects are observed by probing the ladder system from the ground state of the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
5
45
0
Order By: Relevance
“…The underlying physics for such doubly optically resonant processes has already been investigated in many theoretical papers (e.g. [40,41,42]), but only one experiment has been performed up to now, and only at very low excitation energies [43]. An illustration of the expected effect of optical coupling between two autoionization states, here 2s2p…”
Section: Discussionmentioning
confidence: 99%
“…The underlying physics for such doubly optically resonant processes has already been investigated in many theoretical papers (e.g. [40,41,42]), but only one experiment has been performed up to now, and only at very low excitation energies [43]. An illustration of the expected effect of optical coupling between two autoionization states, here 2s2p…”
Section: Discussionmentioning
confidence: 99%
“….) has been given with details elsewhere (see [9]), as well as the density matrix formalism used to calculate the ionization yield. Under the usual approximations (dipole, rotating wave approximations .…”
Section: Theoretical Approachmentioning
confidence: 99%
“…A probe laser couples the 3s ground state to the 3sks and 3skd continua through two-photon absorption, a second laser (coupling laser) couples these continua to the upper 3p3d PM doubly excited state. Such a scheme has been already studied (both experimentally and theoretically) by Karapanagioti et al [8,9], but emphasis was put on the resonant coupling of 3p3d PM and 3p SC autoionizing states. Nevertheless, Karapanagioti et al [9] have shown an experimental spectra (see Fig.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The electron energies (reported in table I) are deduced from the energy conservation principle excluding laser induced level shifts. The atomic structure calculations providing the atomic energy levels and the transition cross-sections have been described in detail in a precedent paper [15]. The energies and wave-functions are computed using a frozen-core configuration interaction (CI) procedure.…”
Section: B Theoretical Modelingmentioning
confidence: 99%